Structural implications of Pseudomonas fluorescence strain AMS8 cold-active lipase in organic solvent - Yaacob, Norhayati (2018)
Cold-active lipases from bacterial sources could benefit the enzyme industry significantly due to its adaptive structural features which makes it active at low temperature and flexible at low water medium. Unfortunately, there was lack of understanding regarding the structure adaptation of cold-active lipase in organic solvent. This study embarks on studying structure-function relationship of family I.3 cold-active AMS8 lipase in selected organic solvents. Cold-active AMS8 lipase was catalytically active at 25 – 45 °C and has two alpha-helix lids, a pentapeptide motif with nucleophilic-serine and repeat-toxin sequence motifs distribution at C-terminus. The experiment begins with structure prediction of AMS8 lipase by Small Angle X-ray Scatterings (SAXS) and homology modeling. AMS8 lipase ab-initio model from SAXS was found to be similar with the homology model and MIS38 Pseudomonas lipase structure. Following this, molecular dynamics (MD) simulations and docking analyses were performed with homology-modelled lipase where ethanol, toluene, dimethyl sulfoxide and 2-propanol have shown interactions with active site residues. Toluene achieved the highest energy binding (4.92 kcal/mol) with AMS8 lipase and strongly interacts with Ser-204, Gly-205 and His-206. Based on simulations in toluene, a strong hydrogen bond was formed at catalytic site between Gly-210 and Ser-238, but weaker hydrogen bond was found at lid 2 between Gly-156 and Ser-160. An increase in α-helices structure could be subjected to enzyme surface interference by toluene. AMS8 lipase also exhibited higher number of disallowed region when simulated in toluene (1.9 %) and hexane (3.2 %). Methanol and toluene showed improvements in AMS8 lipase substrate binding (p-nitrophenol palmitate) but slows down the catalytic rate, kcat. Based on these characterizations, site-directed mutagenesis was applied on regions with high accessibility to toluene. Leu-208 located next to polar Ser-207 was chosen as a mutation site because of the high solvent-accessible surface area and was located within aggregation-prone sites. Substitution of leucine to alanine ruined hydrogen bond that formed between Ser-238 and Gly-210 causing the tunnel to collapse. Following this, a reduction in substrate affinity for pNPP and pNPL was observed in 0.5 % (v/v) toluene. The enhanced stability of L208A was contributed by increase in aggregation and denaturation points which made it easy to adapt at slightly high temperature, 45 °C. Mutating Thr-52 and Gly-55 to tyrosine on lid 1 area stabilizes the protein conformation and improves the surface recognition of toluene due to the presence of aromatic side chain. Presence of tyrosine at lid 1 did not draw electrostatic interactions on the protein surface for substrate binding but being there, the local flexibility on both surface and catalytic site embraced positive changes to lipase activity. Mutant T52Y favours pNPP (C16) but G55Y hydrolysed smaller pNPC (C8) in aqueous solvent. Both lid 1 mutants favoured pNPC when reacted in 0.5 % (v/v) toluene. Although binding improvements of long-chain substrate was evident in T52Y, its activity in toluene remained low in comparison to the recombinant. In characterisation study, lid 1 mutants have lower optimal temperature compared to its recombinant and L208A. Mutant T52Y has the longest half-life in aqueous medium at 25 and 37 °C while exhibited longer half-life in 0.5 % (v/v) toluene at 25 °C. Both lid 1 mutants were stable in toluene up to 3 % (v/v) concentration. In 0.5 % (v/v) toluene, all lipases aggregated at higher temperature but denaturation happened at lower temperature for lid 1 mutants. Unlike others, mutant T52Y displayed increased values of enthalpy and entropy from 0 to 5 % (v/v) toluene showing improvements of protein stability and decline in catalytic rate. All lipases exhibited no structure loss due to the unchanged and minimal increase of its entropy value in toluene at 25 to 35 °C. In conclusion, adaptations of cold-active lipase AMS8 in toluene (0.5 - 5 %, v/v) at temperatures 20 - 35 °C was factorised by lid 2 flexibility, formations of substrate-tunnel, hydrogen bond in catalytic area, alpha-helix reduction, higher aggregation points, low enthalpy and a slight increase in entropy.